2013
DOI: 10.1038/npp.2013.5
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Granule Neuron Number and Dentate Gyrus Volume in Antidepressant-Treated and Untreated Major Depression

Abstract: Smaller hippocampal volume is reported in major depressive disorder (MDD). We hypothesize that it may be related to fewer granule neurons (GN) in the dentate gyrus (DG), a defect possibly reversible with antidepressants. We studied age-, sex-, and postmortem interval-matched groups: no major psychopathology (controls); unmedicated-MDD; and MDD treated with serotonin reuptake inhibitors (MDD*SSRI) or tricyclics (MDD*TCA). Frozen right hippocampi were fixed, sectioned (50 mm), immunostained with neuronal nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
214
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 302 publications
(234 citation statements)
references
References 39 publications
17
214
0
3
Order By: Relevance
“…Furthermore, a recent in-vivo MRI study we performed (Huang et al, 2013) and post-mortem studies (Boldrini et al, 2013), reported increased DG volume and increased DG granule cell and glial cell numbers (Cobb et al, 2013) in MDD patients treated with antidepressants. These findings are consistent with the suggestion that stimulating DG neurogenesis with antidepressants might play an important role in reversing HC volume reduction in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent in-vivo MRI study we performed (Huang et al, 2013) and post-mortem studies (Boldrini et al, 2013), reported increased DG volume and increased DG granule cell and glial cell numbers (Cobb et al, 2013) in MDD patients treated with antidepressants. These findings are consistent with the suggestion that stimulating DG neurogenesis with antidepressants might play an important role in reversing HC volume reduction in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preclinical studies have shown that stress-and glucocorticoid-induced suppression of DG neurogenesis can be prevented or reversed by antidepressant treatments, which also have direct neurogenic effects (Czéh et al, 2001;Pittenger and Duman, 2008;). In turn, recent post-mortem studies (Boldrini et al, 2013) and high field MRI studies (Huang et al, 2013) reported increased volume of the DG in MDD patients on antidepressant medications when compared to unmedicated MDD patients.…”
Section: Introductionmentioning
confidence: 98%
“…They reported that participants with current depression, defined as a Center for Epidemiologic Studies-Depression Scale score X4 or current antidepressant use, had smaller hippocampal volumes. Studies in both living depressed patients (Sheline et al, 2003) and postmortem analyses (Boldrini et al, 2013) suggest that antidepressants may modify the association between hippocampal volume and depression. However, in the current report none of the analyses suggested a relationship between hippocampal volume and antidepressant, or other psychotropic medication use.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether a decrease in hippocampal DG volume in antidepressant treated and untreated individuals suffering from MDD is a result of decreased neurogenesis, mature granule neuron number and DG and granule cell layer volume were determined (Boldrini et al 2013). Boldrini et al found that untreated MDD patients had fewer mature granule neurons in the anterior hippocampal DG than antidepressant treated or control individuals (a result consistent with imaging studies of McKinnon et al [2009]), as well as smaller DG and granule cell layer volumes (estimated stereologically using the Cavalieri method).…”
Section: Hippocampusmentioning
confidence: 99%